Variability of issr markers and estimation of inheritance of diagnostic characters among StY-genome species of Elymus pendulinus, E. brachypodioides and E. vernicosus (Poaceae: Triticeae) - E. V. Kobozeva; S. V. Asbaganov; O. V. Dorogina; A. V. Agafonov (Вавиловский журнал генетики и селекции, 2017)
Currently three species are recognized in Russia within the genus Elymus subsection Pendulini, namely, E. pendulinus, E. brachypodioides and E. vernicosus. The degree and quality of lemma and stem node vestitures and ecology are considered important characters for species delineation. In Primorsky krai and Altai Republic we have found a number of mixed populations in which there is visually continuous variation in lemmas vestitures from being completely glabrous to densely puberulent or pilose. Additionally, there are a number of populations in Primorsky krai in which individuals having either smooth or pilous stem nodes grow together. A study of polymorphism of ISSR markers among selective accessions of three species from different locations was carried out together with the reference species E. ciliaris and E. gmelinii. The consensus dendrogramm constructed by results of ISSR markers has shown no taxon specific patterns in accessions of the subsection Pendulini. Hybrids between the individuals of different species of the subsection in six cross combinations have been created. All F1 plants had normally developed open anthers, seed fertility (SF) ranged from 8 % to 89 % in different combinations. In F2 populations no sterile individuals or increase of SF up to normal values were observed. Hence, three taxa form a unified recombination gene pool. The diagnostic characters were found to be controlled by one pair of alternative alleles for glabrous vs. hairy stem nodes, and by one or two pairs of alleles in different cross combinations for glabrous vs. hairy lemmas. These characters can be considered as normal inter- and/or intra-population variation. Therefore, E. brachypodioides and E. vernicosus need to be relegated to infraspecific rank within Elymus pendulinus s. l. as varieties.